Endogenous Mesenchymal Stromal Cells in Bone Marrow Are Required to Preserve Muscle Function in mdx Mice. (March 2015) - Fujita, Ryo; Tamai, Katsuto; Aikawa, Eriko; Nimura, Keisuke; Ishino, Saki; Kikuchi, Yasushi; Kaneda, Yasufumi
Abstract The physiological role of "endogenous" bone marrow (BM) mesenchymal stromal cells (MSCs) in tissue regeneration is poorly understood. Here, we show the significant contribution of unique endogenous BM‐MSC populations to muscle regeneration in Duchenne muscular dystrophy (DMD) mice (mdx). Transplantation of BM cells (BMCs) from 10‐week‐old mdx into 3–4‐week‐old mdx mice increased inflammation and fibrosis and reduced muscle function compared with mdx mice that received BMCs from 10‐week‐old wild‐type mice, suggesting that the alteration of BMC populations in mdx mice affects the progression of muscle pathology. Two distinct MSC populations in BM, that is, hematopoietic lineage (Lin)−/ckit−/CD106+/CD44+ and Lin−/ckit−/CD106+/CD44− cells, were significantly reduced in 10‐week‐old mdx mice in disease progression. The results of a whole‐transcriptome analysis indicated that these two MSC populations have distinct gene expression profiles, indicating that the Lin−/ckit−/CD106+/CD44+ and Lin−/ckit−/CD106+/CD44− MSC populations are proliferative‐ and dormant‐state populations in BM, respectively. BM‐derived Lin−/CD106+/CD44+ MSCs abundantly migrated to damaged muscles and highly expressed tumor necrosis factor‐alpha‐stimulated gene/protein‐6 (TSG‐6), an anti‐inflammatory protein, in damaged muscles. We also demonstrated that TSG‐6 stimulated myoblast proliferation. The injection of Lin−/ckit−/CD106+/CD44+ MSCs into the muscle of mdx mice successfully ameliorated muscle dysfunction by decreasing inflammation and enhancing muscle regeneration through TSG‐6‐mediated activities. Thus, we propose a novel function of the unique endogenous BM‐MSC population, which countered muscle pathology progression in a DMD model. Stem Cells2015;33:962–975